Juegos como estimulación temprana para el desarrollo de la motricidad fina en los estudiantes de la unidad educativa Adolfo María Astudillo de la parroquia camilo Ponce del cantón Babahoyo durante el año 2017 - Torres Montes, Mónica Maribel (2017)
It is the development of fine motor skills, is the result of the achievements of the child in the domain of fine movements of the hand, feet, eye-hand coordination, pedal oculus, spatial orientation and laterality, under the influence of the adult, who intentionally or not, shows him the socially established modes of motor behavior, which allow the child to develop their independence, perform increasingly complex actions and improve them. Pre-school age is considered the moment in which stimulation is a determinant of development by a series of factors that provide it: accelerated growth, the development of sensory systems, the osteomyoarticular system (flexibility of muscles and tendons, calcification of the bones, presenting in the hand, in the foot, in the musculature of the face different stages of maturation), the faculty of establishing innumerable temporal nervous connections, as well as the process of myelogenesis, which constitute the physiological basis that allow to configure the conditions for learning the different actions. Associated to these are the critical or sensitive periods of development, the infinite capacity to assimilate the social experience transmitted by the adult, and not least, the child's own individual experience, including contents related to the development of fine motor skills which is directed to the necessary exercise and development of the small muscle groups of the face hands fingers and toes-fingers, since they usually do not receive the direct intention when performing the rest of the exercises related to gross motor, considering important the work of they are part of the integral development of the child, which will contribute to the realization of more precise movements in their future evolution